2021
DOI: 10.1021/acs.jpclett.1c02310
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Determines the Switch in the Fibril Forming Regions in the Low-Complexity FUS Protein and Its Variants

Abstract: Residues spanning distinct regions of the low-complexity domain of the RNA-binding protein, Fused in Sarcoma (FUS-LC), form fibril structures with different core morphologies. Solid-state NMR experiments show that the 214-residue FUS-LC forms a fibril with an S-bend (core-1, residues 39–95), while the rest of the protein is disordered. In contrast, the fibrils of the C-terminal variant (FUS-LC-C; residues 111–214) have a U-bend topology (core-2, residues 112–150). Absence of the U-bend in FUS-LC implies that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(87 citation statements)
references
References 44 publications
8
79
0
Order By: Relevance
“…These molecular polymorphisms are assumed to be derived from differences in the number, relative orientation, and internal substructure of the protofilaments. Recent simulation studies have shown that the sequence-specific conformational heterogeneities of monomer ensembles are crucially associated with their aggregation propensities and the fibril polymorphisms can be caused by changes in the population of fibril-like states in the monomeric structures [ 56 , 57 ].…”
Section: Structural Polymorphism Of Amyloid Fibrilsmentioning
confidence: 99%
“…These molecular polymorphisms are assumed to be derived from differences in the number, relative orientation, and internal substructure of the protofilaments. Recent simulation studies have shown that the sequence-specific conformational heterogeneities of monomer ensembles are crucially associated with their aggregation propensities and the fibril polymorphisms can be caused by changes in the population of fibril-like states in the monomeric structures [ 56 , 57 ].…”
Section: Structural Polymorphism Of Amyloid Fibrilsmentioning
confidence: 99%
“…It not only accounts for the possibility of fibril polymorphism, but also provides a basis for understanding the aggregation propensities of different peptide sequences. 29,32…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our work, 29 underscores the importance of quantitatively characterizing the N* states present within the monomer conformational ensemble of assembly-competent IDPs in order to provide a microscopic basis for protein aggregation. 29,32…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations